Teach yourself... powerpoint for windows 95 - Badgett, Tom. ([S.l.] : Mis Pr, 1995)
This book thoroughly introduces all the new features of PowerPoint in the enhanced Windows 95 environmen t. It gives step by step instructions for designing presenta tions, composing slide shows, using templates and more. '